The perception of muslim towards jihad and terrorism / Hazira Athirah Abd Halim and Nor Amalina N Junaidi Sulong - Abd Halim, Hazira Athirah; N Junaidi Sulong, Nor Amalina (2016)
Jihad is one of the international issue that always been arise and it is always been related to the terrorism. In the general context, jihad means struggle and strive against negative thought, negative action and aggression against a person, family, society or country. Usually, jihad is considered associated with Islam and Muslims only (Shaykh Hisham Kabbani, n.d). The term of jihad is always being abuse by militant groups in order to achieve their own personal interest. In Islam, jihad can be defines as striving and struggling for improvement and fighting back to defend back on what is they are belong to such as honor, assets and homeland. Nowadays, Muslims being called as terrorist when they are trying to defend by fighting back with struggle to get back their right and what they are belong to such as honor, assets and homeland. Some perception said that they are being called terrorism because they are using inappropriate way to get back what their own. A review of the literature about terrorism reveals that terrorism itself is difficult to define. While clear objectives definitions of terrorism are easy to develop, simple definitions get complicated by two main factors. First, every terrorist commits his actions in support of a cause that many others also support, and people find it difficult to acknowledge that actions taken in support of their pet cause could be terrorist acts and second is governments and media outlet consistently apply, misapply, or refuse to apply the term terrorism based on political factor (Shaykh Hisham Kabbani, n.d). Malaysia itself is a country that also can be possibly receiving terrorism attacks as recently, few cases related to militant group such as ISIS and Daesh being actively working in this country.